Effect of Entrepreneurship Competency, Market Orientation, And Entrepreneurial Orientation on Business Performance In Herbal Msmes Medan City - Lidya Kusuma Sari; Ami Dilham; Inneke Qamariah; Arif Qaedi Hutagalung (TALENTA Publisher, Universitas Sumatera Utara, 2022)
This study aims to determine and analyze the effect of entrepreneurial competence, market orientation and entrepreneurial orientation on the business performance of MSME factories in the city of Medan. This research is a peer-reviewed research and the type of data used is quantitative and raw data obtained through interviews and questionnaires to the MSMEs of herbal medicine in Medan City with the assistance of the Medan City Cooperatives and MSMEs Service. Led by the Ministry of Cooperatives and MSMEs in Medan City, the authors of this study conducted a survey of 41 MSMEs of Chinese herbal medicine in Medan City. The author's sample size is 41 SME factories in Medan City, with the help of Medan City Cooperatives and SMEs for saturated sampling. The data analysis technique used is multiple linear regression analysis. The results of this study indicate that simultaneously entrepreneurial ability, market orientation and entrepreneurial orientation have a positive and significant impact on the business performance of MSMEs in the Medan factory. The results of the study partially show that entrepreneurial ability, market orientation and entrepreneurial orientation have a positive and significant impact on the business performance of the Medan MSME factory.